Linear Focal Elastosis Following Striae Distensae: Further Evidence of Keloidal Repair Process in the Pathogenesis of Linear Focal Elastosis - Jeong, Jin Seob (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Linear focal elastosis (LFE) is a rare dermal elastosis characterized by hypertrophic yellowish linear plaques and increased abnormal elastic tissues in the lumbosacral area. Although the pathogenesis of this disorder remains unknown, it may be associated with keloidal repair process (KRP) of elastic tissues in striae distensae (SD), because there have been some reported cases of LFE accompanied by SD. We herein report a 14-year-old boy with LFE following SD in the lumbar region. Our case supports the hypothesis of KRP in the pathogenesis of LFE. Immunohistochemical study for transforming growth factor-beta (TGF-β) was negative. Therefore, we assume that the pathogenesis of KRP in LFE is different from that of keloid development, which is the TGF-β signaling pathway.